Diethyl ether as self-healing electrolyte additive enabled long-life rechargeable aqueous zinc ion batteries. (August 2019) - Xu, Weina; Zhao, Kangning; Huo, Wangchen; Wang, Yizhan; Yao, Guang; Gu, Xiao; Cheng, Hongwei; Mai, Liqiang; Hu, Chenguo; Wang, Xudong
Abstract: Aqueous rechargeable zinc ion batteries (ARZIBs) is considered one of the most compelling candidates for grid-scale energy storage owing to their cost effectiveness, good safety, eco-friendliness, high output voltage, and high capacity. However, their practical applications are still largely limited by the undesirable cyclability and high-rate capability. Here, we report a discovery that using a small amount (2 vol%) of diethyl ether (Et2 O) as the electrolyte additive could largely improve the performance of Zn–MnO2 batteries. The addition of Et2 O yielded the first cycle coulombic efficiency of 95.6% at 50 mA/g, a high capacity of 115.9 mAh/g at 5 A/g and 97.7% retention of initial capacity after 4000 cycles, demonstrating an outstanding rate capability and cycling performance among the reported Mn-based zinc ions batteries in mild electrolyte. Ex-situ characterizations revealed that appropriate amount of Et2 O molecules could effectively suppress the formation of Zn dendrites on Zn anode, which is the main mechanism for cyclability improvements. Graphical abstract: Aqueous Zn–MnO 2 battery with 2 vol% diethyl ether (Et 2 O) electrolyte additive exhibited significantly improved cycling stability, especially at high rates. The improvement was attribute to the effective suppression of dendrite formation on Zn metal anodes.Image 1 Highlights: Et2 O as electrolyte additive successfully improves the coulombic efficiency of Zn–MnO2 battery. A high capacity retention of 97.7% of the Zn–MnO2 with Et2 O is achieved after 4000 cycles at 5 A/g. The Zn–Zn symmetrical battery with Et2 O electrolyte additive sustains for over 250 h at 0.2 mA/cm 2 . The highly-polarized Et2 O molecules preferably adsorb on Zn extrusions, suppressing dendrite formation.